Phytochemical and Biological Studies on Essential Oil and Leaf Extracts of Gaultheria fragrantissima Wall - Joshi, S; Subedi, PC (Nepal Journal of Science and Technology, 2014)
Essential oil of Gaultheria fragrantissima Wall was isolated by hydrodistillation and GC/MS was used to find out the active constituents present in the oil. Methyl salicylate was the major compound (94.16%) and 4-hydroxy-4- methyl-2-pentanone as minor (5.84%) of oil. Phytochemical screening of methanol, ethyl acetate, chloroform and hexane extracts of leaves showed the presence of volatile oils, alkaloids, carotenoids, steroids, triterpenes, fatty acids, phenolic compounds and glycosides. Brine Shrimp Bioassay showed the oil was cytotoxic having LC50 value of 81.3 mg/l. Oils having 50% and 100% were found to be biologically active towards Staphylococcus and Kelbesia species but no positive activity was noted against Proteus and Escherichia species. Both concentrations (50% & 100%) of ethyl acetate and hexane extracts were biologically active only towards Proteus species. Further, chloroform extract was biologically inactive among the tested species. E. coli and S. aureus showed greater zone of inhibition towards methanol extracts for both concentrations. DOI: http://dx.doi.org/10.3126/njst.v14i2.10416 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 59-64